Evidence of hybridization, mitochondrial introgression and biparental inheritance of the kdna minicircles in trypanosoma cruzi i - Rusman, Fanny (2020)
Background Genetic exchange in Trypanosoma cruzi is controversial not only in relation to its frequency, but also to its mechanism. Parasexual genetic exchange has been proposed based on laboratory hybrids, but population genomics strongly suggests meiosis in T. cruzi. In addition, mitochondrial introgression has been reported several times in natural isolates although its mechanism is not fully understood yet. Moreover, hybrid T. cruzi DTUs (TcV and TcVI) have inherited at least part of the kinetoplastic DNA (kDNA = mitochondrial DNA) from both parents. Methodology/Principal findings In order to address such topics, we sequenced and analyzed fourteen nuclear DNA fragments and three kDNA maxicircle genes in three TcI stocks which are natural clones potentially involved in events of genetic exchange. We also deep-sequenced (a total of 6,146,686 paired-end reads) the minicircle hypervariable region (mHVR) of the kDNA in such three strains. In addition, we analyzed the DNA content by flow cytometry to address cell ploidy. We observed that most polymorphic sites in nuclear loci showed a hybrid pattern in one cloned strain and the other two cloned strains were compatible as parental strains (or nearly related to the true parents). The three clones had almost the same ploidy and the DNA content was similar to the reference strain Sylvio (a nearly diploid strain). Despite maxicircle genes evolve faster than nuclear housekeeping ones, we detected no polymorphisms in the sequence of three maxicircle genes showing mito-nuclear discordance. Lastly, the hybrid stock shared 66% of its mHVR clusters with one putative parent and 47% with the other one; in contrast, the putative parental stocks shared less than 30% of the mHVR clusters between them. Conclusions/significance The results suggest a reductive division, a natural hybridization, biparental inheritance of the minicircles in the hybrid and maxicircle introgression. The models including such phe-nomena and explaining the relationships between these three clones are discussed.